ISLAMIC THOUGHT AND DA'WAH TRANSFORMATION IN THE DIGITAL ERA - Nadia, Nadia; Rifa'i, Akhmad (Universitas Islam Madura, 2025)
The digital era has significantly changed the attitude of Islamic da'wah, encouraging dai and ulama to adapt da'wah methods and approaches to be more relevant and effective. This research aims to explore contemporary Islamic thought related to the transformation of da'wah in the midst of the development of digital technology. The research method used is a literature study with a qualitative approach, examining various sources of literature, journals, scientific articles, and case studies related to the implementation of digital da'wah. The results of this study show that Islamic thought and the transformation of da'wah in the digital era have five things that include Islamic thought in the context of da'wah, the transformation of da'wah in the digital era, changes in da'wah media, the use of technology to improve the quality of da'wah, and the dissemination of Islamic messages at a higher speed. Thus, this digital era shows that the transformation of da'wah in the digital era not only involves changes in media and platforms but also demands new approaches in delivering messages that are in accordance with the characteristics of modern audiences. Islamic thinking about da'wah now involves a more inclusive strategy, the use of communication technology, and the use of social media to reach a wider audience. In addition, digital da'wah faces challenges such as misinformation, polarization, and limited direct interaction. The implications of the research are that ethical guidelines and the development of digital literacy are needed for Dai to maintain the integrity of Islamic da'wah.